Milk quality and antimicrobial resistance against mastitis pathogens after changing from a conventional to an experimentally organic dairy farm - Witaya Suriyasathaporn (2018)
The present study was to investigate the effect of the transition from conventional to organic dairy farming on the antimicrobial resistant pattern of pathogens in milk. A farm with tie-stall management, with an average herd size of 20 milking cows, was selected based on the owner's willingness to accept, for at least 6 months, the highly restricted protocol developed in this study. Comparisons of bacterial isolates and antimicrobial susceptibilities before changing to an organic farm system (BEFORE) and for 6 months after (AFTER) operating the experimental organic farm system were performed by Fisher's Exact Chi-square tests. Significant levels were defined at p<0.05. During the AFTER period, average frequency of antibiotic treatment was decreased from more than 3 cases/month to less than 1 case/month during which the antibiotic use was authorized only by the veterinarian. In total, 92 and 70 quarter milk samples from 24 and 18 cows during BEFORE and AFTER, respectively, were included in the study. Overall, isolates ranged from a non-resistant level for cephazolin to a very high resistant level to streptomycin (64.71% to 95.45%). Percentages of antimicrobial resistant isolates during BEFORE were significantly higher than during AFTER for ampicillin (43.48% and 5.88%, respectively) and streptomycin (95.45% and 64.71%, respectively). In conclusion, percentages of antimicrobial resistant isolates were decreased after 6 months of operating as an organic farm system.